2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9013241
|View full text |Cite
|
Sign up to set email alerts
|

Directional Wideband Channel Measurements at 28 GHz in an Industrial Environment

Abstract: With the expected adoption of millimeter wave technologies for industrial communication, it is fundamentally important to properly understand the radio channel characteristics of such environments. This paper presents the setup, scenario and results of a measurement campaign at 28 GHz in a machine hall. The radio channel was measured with a bandwidth of 2 GHz and both large scale parameters and directional information were extracted. Evaluation of the power delay profiles shows that the channel contains dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
4
26
0
Order By: Relevance
“…Tremendous progress is observed in understanding the nature of wave propagation in industrial environments at both sub-6-GHz and mmWave frequencies (see [56] and [160]- [162] for a taxonomy). Naturally, the typical industrial environment is unlike the residential or other indoor environments since the effects of mechanical and electrical noise, as well as interference, are high due to the broad operating temperatures, heavy machinery, and ignition systems [56], [160], [161], [163]. Generally, industrial buildings are taller than ordinary office buildings and are sectioned into several working areas, between which there usually exist straight aisles for transportation of materials or for human traffic.…”
Section: Propagation In Industrial Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tremendous progress is observed in understanding the nature of wave propagation in industrial environments at both sub-6-GHz and mmWave frequencies (see [56] and [160]- [162] for a taxonomy). Naturally, the typical industrial environment is unlike the residential or other indoor environments since the effects of mechanical and electrical noise, as well as interference, are high due to the broad operating temperatures, heavy machinery, and ignition systems [56], [160], [161], [163]. Generally, industrial buildings are taller than ordinary office buildings and are sectioned into several working areas, between which there usually exist straight aisles for transportation of materials or for human traffic.…”
Section: Propagation In Industrial Environmentsmentioning
confidence: 99%
“…The study in [164] proposes a double-directional model with parameters that are tailored at 5 GHz from measured data. A detailed comparison between propagation characteristics at 3.7 and 28 GHz is presented over a bandwidth of 2 GHz in [161], where LOS and NLOS pathloss exponents different to those seen in [162] are reported due to the environmental differences. No substantial difference in the delay spread is seen across the two bands of 3.7-28 GHz.…”
Section: Propagation In Industrial Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio propagation measurements at the sub-THz band in indoor industrial environments are expected to attract more research interest [ 40 ]. For instance, a few mmWave radio propagation measurements have been conducted in various industrial environments at 28 GHz [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and 60 GHz [ 44 , 51 , 52 ]. Narrowband measurements were conducted inside a factory environment at 28 GHz in [ 46 ] to study the path loss at a 5–100 m distance over 400 LoS and NLoS measured points, and it was shown that the PLE values were 2 and 4.1 for LoS and NLoS, respectively.…”
Section: Overview Of Radio Propagation Measurements In Industrial mentioning
confidence: 99%
“…Based on the conducted wideband measurements at 28 GHz in an engineering workshop, it was observed that the reflected and refracted mmWave propagation waves from metallic surfaces were significantly high [ 47 ]. In [ 49 ], based on wideband time domain measurements at 28 GHz with a 2 GHz bandwidth inside a circle-shaped machine hall, the path loss and RMSDS were investigated. It was found that the PLEs of the FI model were 1.9 and 0.9 for LoS and NLoS, respectively, and 1.8 and 2 based on the CI model for LoS and NLoS, respectively.…”
Section: Overview Of Radio Propagation Measurements In Industrial mentioning
confidence: 99%